Educational Values in the Design of Iraqi Stamps as an Identity Revival Element after 2003 (The International Journal of Educational Sciences and Arts, 2024)
The current study aims to identify the educational values in the design of Iraqi stamps and their reflection in reviving the concept of identity.The research problem is outlined in the question about the nature of the educational values in the design of Iraqi stamps and their reflection in reviving the concept of identity after 2003.The research hypotheses are:1- The Iraqi stamp has a national identity after 20032- The Iraqi stamp has educational and aesthetic valuesThe previous studies are reviewed next followed by sections of the theoretical framework. The first section is about the concept of educational values. The second section explains the concept of identity and its nature, and the third section is dedicated to Iraqi stamps and their characteristics.In regards to the research procedures, the research community was limited to the Iraqi stamps issued after 2003, which were (484) stamps, with (4) stamps being excluded due to poor printing. Then, the stamps were divided into topics consistent with educational values ​​for convenience of analysis. The result is (5%) of each topic was equivalent to (25) models or stamps. After adopting observation as an approach of research and a system of indicators of the theoretical framework, a model analysis form was designed to obtain a set of results, the most important of which are:Aesthetic values was on the top of list by (80) recurrences, with the highest recurrence rate of up to (35.24%), which indicates the aesthetics, organization and organization of stamps. Moreover, postage stamps carried multiple functions, including, social, historical, economic and cultural identity.The study is finalized with the following conclusions:1-     The Iraqi postal stamp after 2003 carried a national identity.2-     The Iraqi postal stamp has aesthetic and historical values that bear the features of the Iraqi environmental heritage.
Keywords: Postage Stamp; National Identity; Iraq After 2003; Post-War Iraq